Exploring the effect of lexicality and listener experience on gradient ratings of Swedish sibilant fricatives. - Wikse Barrow, Carla; Ottosson, Lina; Strömbergsson, Sofia (Clinical Linguistics & Phonetics, 2025)
This study explores the influence of lexicality on gradient judgments of Swedish sibilant fricatives by contrasting ratings of initial fricatives in words and word fragments (initial CV-syllables). Visual-Analogue Scale (VAS) judgments were elicited from experienced listeners (speech-language pathologists; SLPs) and inexperienced listeners, and compared with respect to the effects of lexicality using Bayesian mixed-effects beta regression. Overall, SLPs had higher intra- and interrater reliability than inexperienced listeners. SLPs as a group also rated fricatives as more target-like, with higher precision, than did inexperienced listeners. An effect of lexicality was observed for all individual listeners, though the magnitude of the effect varied. Although SLP's ratings of Swedish children's initial voiceless fricatives were less influenced by lexicality, our results indicate that previous findings concerning VAS ratings of non-lexical CV-syllables cannot be directly transferred to the clinical context, without consideration of possible lexical bias.